The Effect of Ocean Salinity on Climate and Its Implications for Earth's Habitability. Issue 10 (24th May 2022) - Olson, Stephanie; Jansen, Malte F.; Abbot, Dorian S.; Halevy, Itay; Goldblatt, Colin
Abstract: The influence of atmospheric composition on the climates of present‐day and early Earth has been studied extensively, but the role of ocean composition has received less attention. We use the ROCKE‐3D ocean‐atmosphere general circulation model to investigate the response of Earth's present‐day and Archean climate system to low versus high ocean salinity. We find that saltier oceans yield warmer climates in large part due to changes in ocean dynamics. Increasing ocean salinity from 20 to 50 g/kg results in a 71% reduction in sea ice cover in our present‐day Earth scenario. This same salinity change also halves the p CO2 threshold at which Snowball glaciation occurs in our Archean scenarios. In combination with higher levels of greenhouse gases such as CO2 and CH4, a saltier ocean may allow for a warm Archean Earth with only seasonal ice at the poles despite receiving ∼20% less energy from the Sun. Plain Language Summary: The composition of the atmosphere, especially the abundance of greenhouse gases, famously influences Earth's climate system. We use a climate model to show that the composition of the ocean can also have a major impact on surface temperature and ice cover. We focus specifically on the amount of salt dissolved in seawater, and we find that saltier oceans tend to result in warmer climates. These effects are modest today, but salt may be a key ingredient for early Earth habitability in the distant past when the Sun was less bright. Key Points: Saltier oceans result in warmer climates with less sea ice Warming with increasing salinity is strongly affected by changing ocean dynamics A saltier ocean may have helped keep early Earth warm when the Sun was less luminous